2015
DOI: 10.1152/japplphysiol.00301.2015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of lipid mediators in response to repeated eucapnic voluntary hyperpnea in asthmatic subjects

Abstract: Exercise-induced bronchoconstriction displays refractoriness manifested as a decreased response to repeated exercise challenge within hours. The refractoriness may be attenuated by inhibition of the biosynthesis of prostaglandins (PG). The aim of the study was to determine which PGs and other lipid mediators are excreted during the refractory period. First, 16 subjects with mild stable asthma performed two repeated 4-min challenges with eucapnic voluntary hyperpnea (EVH) 1 and 3 h apart. There was a similar de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…However, this metabolite was not detected by using mass spectrometry, extending earlier data indicating that the 10% cross-reactivity of the antibody against 11b-PGF 2a with 2,3-dinor-11b-PGF 2a explains the results of using that particular EIA on urine. 12,15 We confirmed good agreement between the 2 measurements by using Bland-Altman analysis (see Fig E3 in this article's Online Repository at www.jacionline.org).…”
Section: Effects Of Montelukast On Sputum Cellssupporting
confidence: 69%
See 1 more Smart Citation
“…However, this metabolite was not detected by using mass spectrometry, extending earlier data indicating that the 10% cross-reactivity of the antibody against 11b-PGF 2a with 2,3-dinor-11b-PGF 2a explains the results of using that particular EIA on urine. 12,15 We confirmed good agreement between the 2 measurements by using Bland-Altman analysis (see Fig E3 in this article's Online Repository at www.jacionline.org).…”
Section: Effects Of Montelukast On Sputum Cellssupporting
confidence: 69%
“…11 Mass spectrometry measurements of PGD 2 metabolites were compared with the enzyme immunoassay for 11b-PGF 2a (Cayman Chemical), as described previously. 12…”
Section: Measurement Of Urinary Metabolitesmentioning
confidence: 99%
“…No such inhibitor-induced suppression was observed in a study with repeated hyperpnea challenges [34], suggesting that exercise per se and not the level of ventilation might trigger release of protective PGs. This is, however, challenged by an in-vitro study where cyclic stretch of airway epithelial cells increased PGE2 release in a frequency-dependent manner [35] and also by a recent study that showed increased PGE2 concentrations after hyperpnea and significant refractoriness after a subsequent second hyperpnea [36]. It thus seems conceivable that, in the present study, hyperpnea but not NWU stretched the airways enough to release PGE2, reduce EIB severity and improve lung function recovery, possibly via blocking leukotriene-receptors on airway endothelial cells, thereby inhibiting their bronchoconstrictive effects [37].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increase in anti-inflammatory PGE 2 and PGD 2 systemic production after eucapnic hyperventilation-precipitating bronchoconstriction. This may explain the improved symptoms of exercise repeated within hours 20. It has been also shown that this phenotype depends on epithelial injury and increased epithelial 15-LO activity.…”
Section: Lipid Mediators In Specific Asthma Phenotypesmentioning
confidence: 89%
“…Thus, it is commonly preferred to quantify eicosanoid metabolites in urine. However, prostaglandins, isoprostanes, and proresolutionary eicosanoids all undergo extensive inactivation before excretion with urine 20. The urinary products of their breakdown are β-oxidation metabolites.…”
Section: Clinical Studies On Eicosanoids In Asthmamentioning
confidence: 99%